UPAYA PENEGAKAN HUKUM LINGKUNGAN MELALUI PENERAPAN ASAS STRICT LIABILITY - M.Fahmi Al Amruzi (Faculty of Law, Universitas Diponegoro, 2011)
Wrong policy or arrangement of wrong law represent fundamental of damage environment beside wrong technology, culture of consumerisme and of individualistic. For that, idea create regulation of ideal law as those which encouraged by UU No. 32 year 2009 about environmental law. UU No 41 year 1999 about forestry beside other regulation which related to environment may not desist In the regulation for that Sine/ Liability that does not depend on actual negligence or intent to harm. but that is based on the breach of an absolute duty to make something safe.